Obstetric outcomes of twin pregnancies at advanced maternal age: A retrospective study - Caixia Zhu; Malie Wang; Gang Niu; Juan Yang; Zilian Wang (Elsevier, 2018)
Objective: To evaluate obstetric outcomes in twin pregnancies of advanced maternal age (≥35 years). Materials and methods: A retrospective study involved 470 twin pregnancies in a single center from Sep. 1, 2012 to Mar. 31, 2015. Clinical characteristics and obstetric outcomes were recorded and compared among twin pregnancies who were classified as follows: age 20-29, 30-34, 35-39 and ≥40 years. Results: The incidence of gestational diabetes (age 20-29 years 15.8%; 30-34 years 24.3%; 35-39 years 30.4%; ≥40 years 57.1%; p = 0.004) and premature delivery (20-29 years 58.6%; 30-34 years 69.1%; 35-39 years 72.2%; ≥40 years 85.7%; p = 0.001) significantly increased with increasing age whereas spontaneous abortion (20-29 years 27.6%; 30-34 years 11.6%; 35-39 years 11.4%; ≥40 years 0.0%; p = 0.021) decreased in twin pregnancies of advanced maternal age. In addition, the rate of postpartum hemorrhage increased almost continuously by age and advanced maternal age was described as a risk factor for postpartum hemorrhage (age 35-39, adjusted OR 3.377; 95% confidence interval 1729-6.598; p < 0.001; age ≥ 40, adjusted OR 10.520; 95% CI 1.147-96.492; p = 0.037). However, there was no significant difference between advanced maternal age and adverse neonatal outcomes. Conclusion: In twin pregnancies, advanced maternal age experienced significant higher risk of postpartum hemorrhage, gestational diabetes and premature delivery. Neither adverse neonatal outcomes nor stillbirth was significantly associated with maternal age.